PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI DAN LOKASI TERHADAP PROSES KEPUTUSAN PEMBELIAN KAPUR BARUS MEREK BAGUS (Studi Pada Konsumen Giant BSB Semarang) - Diana Yunita Sari, 14.05.51.0264; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2018)
This study aims to determine the effect of product quality, price perceptions, promotion and location to the purchase decisions of the product "BAGUS" camphor (Study on the consumer Giant BSB Semarang ). The population in this study are all consumers who shop at Giant BSB Semarang. Sampling using purposive sampling technique and the number of samples processed into research data as much as 100 respondents. Data were analyzed by using multiple linear regression model. Based on the results of research that has been done shows the quality of products and locations have a significant positive effect on consumer purchasing decisions of the product "Bagus" camphor . While the perception of price and promotion has no significant effect on purchasing decision.Keywords: Product Quality, Price Perception, Promotion, Location and Purchase Decision